Pengaruh Islamicity Performance Index terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Niknik Noor Arafah; Intan Manggala Wijayanti (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Islamicity Performance Index is a method to measure the performance of Islamic banks, not only in terms of finances but also by evaluating the principles of fairness, halalness, and chastity carried out by Islamic banks. The purpose of this study is to determine the effect of the Islamicity Performance Index on the financial performance of Islamic Commercial Banks in Indonesia for the 2017–2021 period. Sharia-compliant commercial banks that meet the criteria are Bank Muamalat, Bank Victoria Syariah, Bank Jabar Banten Syariah, Bank Mega Syariah, Bank Syariah Bukopin, and BCA Syariah. This study employs quantitative methods that are processed with Microsoft Excel and SPSS 23. Data analysis in this study used multiple linear regression; independent variables in this study were the Profit Sharing Ratio, the zakat Performance Ratio, the equitable distribution ratio, and Islamic Income vs. non-Islamic Income, as well as a dependent variable, namely financial performance (ROA). The results show that the Profit Sharing Ratio has a significant negative effect on financial performance, while the zakat Performance Ratio, the equitable distribution ratio, and Islamic Income vs. non-Islamic Income have a significant positive effect on financial performance and have a coefficient of determination of 44.4%. Abstrak. Islamicity Performance Index merupakan metode untuk mengukur kinerja bank syariah, tidak hanya dari segi keuangan saja tetapi juga mengevaluasi prinsip keadilan, kehalalan dan kesucian yang dilakukan bank syariah. Tujuan penelitian ini untuk mengetahui pengaruh Islamicity Performance Index terhadap kinerja keuangan Bank Umum Syariah di Indonesia periode 2017-2021. Bank umum syariah yang memenuhi kriteria yaitu Bank Muamalat, Bank Victoria Syariah, Bank Jabar Banten Syariah, Bank Mega Syariah, Bank Syariah Bukopin, dan BCA Syariah. Penelitian in menggunakan metode kuantitatif yang diolah dengan Microsoft Excel dan SPSS 23. Analisis data pada penelitian ini menggunakan regresi linear berganda, variabel independen pada penelitian ini yaitu Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, dan Islamic Income vs Non Islamic Income serta variabel dependen yaitu kinerja keuangan (ROA). Hasilnya menunjukan bahwa Profit Sharing Ratio berpengaruh negatif signifikan terhadap kinerja keuangan, sedangkan Zakat Performance Ratio, Equitable Distribution Ratio, dan Islamic Income vs Non Islamic Income berpengaruh positif signifikan terhadap kinerja keuangan, dan memiliki koefisien determinasi sebesar 44,4%.